2005
DOI: 10.1128/iai.73.12.8119-8129.2005
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-Specific Regulation of Immunoglobulin Class Switching in Mice Immunized with Malarial Merozoite Surface Proteins

Abstract: Antibodies that bind to Fc receptors and activate complement are implicated in the efficient control of pathogens, but the processes that regulate their induction are still not well understood. To investigate antigen-dependent factors that regulate class switching, we have developed an in vivo model of class switching to immunoglobulin G2b (IgG2b) using the malaria antigen Plasmodium falciparum merozoite surface protein 2 (MSP2). C57BL/6 mice were immunized with recombinant proteins representing discrete domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 60 publications
2
24
1
Order By: Relevance
“…The lack of a predisposition to produce a particular subclass response regardless of the antigen further supports the hypothesis that the factors influencing the subclass response are determined mainly by the antigen rather than the host. Prior studies of mice identified a T-cell epitope in MSP2 that appears to promote cytophilic IgG subclass responses (47). Although polymorphisms in AMA-1 were not associated with differences in subclass responses, it is conceivable that the component of the antibody response directed against the conserved epitopes may have affected our ability to detect differences in subclass responses to allele-specific epitopes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The lack of a predisposition to produce a particular subclass response regardless of the antigen further supports the hypothesis that the factors influencing the subclass response are determined mainly by the antigen rather than the host. Prior studies of mice identified a T-cell epitope in MSP2 that appears to promote cytophilic IgG subclass responses (47). Although polymorphisms in AMA-1 were not associated with differences in subclass responses, it is conceivable that the component of the antibody response directed against the conserved epitopes may have affected our ability to detect differences in subclass responses to allele-specific epitopes.…”
Section: Discussionmentioning
confidence: 76%
“…It is unclear whether individuals have a bias toward producing a specific subclass regardless of the antigen or if instead the IgG subclass response is generated independently for each antigen and how this relates to protective immunity. While factors determining subclass responses to antigens are not clearly defined, antigen properties, host age, cumulative exposure, and genetic determinants have been linked with the nature of subclass responses (2,4,17,33,34,41,42,47,48). Some studies have suggested that increasing age (and therefore malaria exposure) leads to an increasing polarization of IgG subclass responses to merozoite antigens (41,48).…”
mentioning
confidence: 99%
“…Polarized IgG1 responses are also reported for Pf155/RESA (17), crude schizont lysate (33), RAP-1 (44), and MSP-6 (50), while IgG3 responses are seen for a polymorphic C-terminal region (block 2) of MSP-1 (11), MSP-3 (11, 31), MSP-4 (51), and MSP-7 (50). A crucial role for antigens per se in driving these patterns of subclass switching has been confirmed experimentally both in vitro with human B cells (21) and in a mouse model where different recombinant P. falciparum antigens-expressed with the same fusion protein tag and administered with the same adjuvant-induced very different IgG subclasses (47). This raises the important question of whether there are intrinsic features of individual malarial antigens which influence their interactions with antigenpresenting cells, T cells, or B cells, leading to the preferential 19 -or AMA-1-specific IgG1 inhibited the simultaneous generation of IgG3 responses to MSP-2, then significantly less than 25% of sera would give ODs above the median for both.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, alterations in the concentrations of IL-10 and/or gamma interferon produced by APL-restimulated memory T cells may influence the IgG1/IgG3 balance, as shown for human antibody responses to schistosomiasis (37) and, in a model system, murine IgG subclass responses to P. falciparum MSP-2 (47). Shifts in helper T-cell phenotype with increasing age and increasing malaria exposure as a result of encountering APLs during successive infections with genetically distinct malaria parasites might also explain the age and exposure dependence of the IgG3 response reported here.…”
Section: Discussionmentioning
confidence: 99%
“…The IgG subclass produced in response to infection can dramatically affect the ability of humoral immunity to confer protection against disease (17,18). The Abs made in response to soluble Plasmodium vaccine candidate proteins are heavily skewed toward the IgG3 isotype in humans (19,20), which is equivalent to IgG2b in mice (21). In most experimental mouse models of Plasmodium infection, there is a heavy skewing toward an IgG2a or IgG2c isotype during an in vivo infection (22).…”
mentioning
confidence: 99%